THE INTERFACE POSITION OF A BOSE-EINSTEIN CONDENSATE MIXTURE RESTRICTED BY A HARD WALL IN THE DOUBLE-PARABOLA APPROXIMATION - Duy Thanh Pham; Thanh Hai Dang (Tạp chí Khoa học Đại học Đà Lạt)
In this study, we determine the interface position of a binary Bose-Einstein condensate mixture in the prewetting phase, confined by a hard wall, at absolute zero temperature. An approximate analytical result is obtained by employing the double-parabola approximation (DPA) to the quartic potential energy density within the Gross-Pitaevskii (GP) theory. The interface position depends on the control parameter and the chemical potential ratio. Our analytical result shows good agreement with numerical results, which indicates that the DPA is a reliable method. This study provides insights for experiments focused on observing the wetting transition of gases in the Bose-Einstein condensate phase.